Endothelial Cells Produce a Lipoxygenase Derived Chemo-Repellent which Influences Platelet/Endothelial Cell Interactions – Effect of Aspirin and Salicylate - Buchanan, M R; Butt, R W; Magas, Z; Ryn, J Van; Hirsh, J; Nazir, D J (Thrombosis and Haemostasis, 1985)
We performed experiments to determine whether endothelial cells synthesize phospholipid metabolites via the lipoxygenase pathway and whether these metabolites influence platelet/vessel wall interactions. Monolayers of cultured human endothelial cells were incubated with 14C-arachidonic acid and their cyclo-oxygenase and lipoxygenase metabolites were extracted and identified by radioimmunoassay, thin layer chromatography and high performance liquid chromatography. We found that in addition to the membrane-associated production of PGI2, endothelial cells synthesized a cytosol-associated metabolite, LOX, which was presumably derived through the lipoxygenase pathway. Inhibition of LOX was associated with an increase in PGI2 production and inhibition of PGI2 with an increase in LOX production. Under either condition, platelet adhesion to cultured endothelial cells was significantly decreased. In contrast, when both PGI2 and LOX production were inhibited, platelet adhesion to endothelial cells was enhanced. Furthermore, when LOX was bound to a thrombogenic surface, platelet adhesion was significantly decreased whereas when arachidonic acid or 12-HETE was bound to the surface, platelet adhesion was increased. We conclude that endothelial cells produce not only a cyclo-oxygenase metabolite, but also a lipoxygenase metabolite, both of which influence platelet/endothelial cell interactions.
Keywords: Endothelial cell; Lipoxygenase metabolite LOX; Platelet chemo-repellent factor